Dinoflagellate symbionts escape vomocytosis by host cell immune suppression - Jacobovitz, Marie; Rupp, Sebastian; Voss, Philipp A.; Mägele, Ira; Gornik, Sebastian G.; Guse, Annika (Nature microbiology, 2021)
Alveolata comprises diverse taxa of single-celled eukaryotes, many of which are renowned for their ability to live inside animal cells. Notable examples are apicomplexan parasites and dinoflagellate symbionts, the latter of which power coral reef ecosystems. Although functionally distinct, they evolved from a common, free-living ancestor and must evade their host’s immune response for persistence. Both the initial cellular events that gave rise to this intracellular lifestyle and the role of host immune modulation in coral-dinoflagellate endosymbiosis are poorly understood. Here, we use a comparative approach in the cnidarian endosymbiosis model Aiptasia, which re-establishes endosymbiosis with free-living dinoflagellates every generation. We find that uptake of microalgae is largely indiscriminate, but non-symbiotic microalgae are expelled by vomocytosis, while symbionts induce host cell innate immune suppression and form a lysosomal-associated membrane protein 1-positive niche. We demonstrate that exogenous immune stimulation results in symbiont expulsion and, conversely, inhibition of canonical Toll-like receptor signalling enhances infection of host animals. Our findings indicate that symbiosis establishment is dictated by local innate immune suppression, to circumvent expulsion and promote niche formation. This work provides insight into the evolution of the cellular immune response and key steps involved in mediating endosymbiotic interactions.
Gesehen am 01.06.2021